O uso da música como recurso pedagógico no ensino de História - SANTOS, Everton Antônio Reis Dos (2018)
The present work presents an investigation of the possible uses of music as didactic resource by teachers for the learning of History in schools of basic education. The research is descriptive, qualitative, and uses computerized research as a tool for data collection. The information obtained by the research seeks to demonstrate how music can be used as a strategy for the teaching of History. We discuss studies among the published articles, seeking to analyze how music can be used as a pedagogical strategy to contribute to the teaching of History.